Iron Chelates: Production Processes and Reaction Evolution Analysis. Issue 7 (2nd July 2016) - Apicella, Pietro; Cascone, Sara; De Santis, Felice; Lamberti, Gaetano
Abstract : Nowadays, fertilization using synthetic chelates is the most common technique to address iron chlorosis, a disease that affects plant growth. Ethylenediamine-N, N'-bis(o-hydroxyphenyl) acetic acid (EDDHA) is among the most efficient iron chelating agents. To produce EDDHA, a reaction was performed using as reactants phenol, ethylenediamine, glyoxylic acid, and sodium hydroxide. To study the reaction kinetics, samples were withdrawn from the reactor during the reaction and the kinetics was quantified, evaluating the yield evolution during the reaction phase. This study was useful to optimize the reaction time. Then, a catalyst was added to the reaction mixture to analyze its effect on the reaction evolution. Comparing the reaction evolution of the non-catalyzed and the catalyzed reaction protocols, two main results have to be highlighted: the time to reach the final yield is lower than the one proposed in the literature and the used catalyst has a minimum effect on the reaction rate.